Accounting Choices in the Cash Flow Statement: Analysis in Latin American Companies - Nascimento, Denise Fernandes (2020)
ABSTRACTObjective: this study analyzed which characteristics of companies may be associated with accounting choices at DFC in 565 publicly traded companies in Latin American countries, from 2012 to 2016.Method: this study promotes analysis by estimating twelve logistic regression models and using panel data.Originality / Relevance: the study of DFC's accounting choices provides information about changes in net assets, financial structure and the ability of companies to modify resources.Results: The results show that the size of the companies, the negative cash flow and the sector may be related to the choices of interest and dividends received, and dividends paid, indicating that the results for the variables in Brazil are similar to those of Chile and Peru, even in different institutional settings.Theoretical / Methodological contributions: this study contributes by providing an overview of how financial and non-financial companies in different countries show cash flows, especially with regard to DFC's comparability and accounting choices, which can result in increasing operating cash flow. In addition, the study provides evidence of an association between company characteristics and accounting choices at DFC, showing differences in the countries surveyed, in terms of cash flow interests, and, contrary to the objective of regulatory bodies, regarding the standardization of accounting procedures.